2013
DOI: 10.1089/thy.2012.0573
|View full text |Cite
|
Sign up to set email alerts
|

Recent Trends in the Incidence, Geographical Distribution, and Survival From Thyroid Cancer in Wales, 1985–2010

Abstract: The incidence of thyroid cancer has increased in Wales, predominantly due to an increase in papillary cancers. The current geographical distribution of cases does not support a radiation effect in the region. Survival has remained poor for patients over the age of 65 years and those with anaplastic carcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
22
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 30 publications
3
22
1
Order By: Relevance
“…In addition to being consistent with the hospital based histopathological studies that papillary carcinoma is the commonest malignancy of thyroid and its frequency is increasing. Our findings also conform to the recent registry based studies from Finland (Hakala et al, 2012) and Wales (Amphlett et al, 2013); regarding the increasing trend of papillary carcinoma in Europe. Wang et al, (2013) in their study found incidental papillary carcinoma in 147 out of their 709 cases and concluded that these are more common in females.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In addition to being consistent with the hospital based histopathological studies that papillary carcinoma is the commonest malignancy of thyroid and its frequency is increasing. Our findings also conform to the recent registry based studies from Finland (Hakala et al, 2012) and Wales (Amphlett et al, 2013); regarding the increasing trend of papillary carcinoma in Europe. Wang et al, (2013) in their study found incidental papillary carcinoma in 147 out of their 709 cases and concluded that these are more common in females.…”
Section: Discussionsupporting
confidence: 92%
“…Amphlett et al (2013), observed the recent trends in the incidence, geographical distribution, and survival from thyroid cancer in Wales. From Turkey, Veyseller et al (2009), looked into thyroidectomies for benign diseases, while Yildiz et al (2014), studied the rising trends of papillary carcinoma of thyroid.…”
Section: Introductionmentioning
confidence: 99%
“…The proportion of surgeries ex- cluded was constant during 1995-2015, but excluded thyroid hormone therapies increased from 1.2 to 2.6%. This may also be explained by improved survival in thyroid cancer patients [34]. Estimation of only direct medicine and hospital costs produces reliable but conservative estimates likely in the same direction as all direct, indirect, medical, and nonmedical costs.…”
Section: Discussionmentioning
confidence: 99%
“…T hyroid cancer is the most common endocrine malignancy, and its incidence has increased almost threefold in recent decades (1)(2)(3)(4). Papillary thyroid cancer (PTC) is the predominant histologic subtype (85-90%), and has a 10-year survival rate of greater than 90% (5,6).…”
Section: Introductionmentioning
confidence: 99%